2005
DOI: 10.1364/opex.13.000789
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation of thermally poled chalcogenide glass

Abstract: Second harmonic generation (SHG) has been obtained in a sample of Ga5Ge20Sb10S65 glass submitted to a thermal poling treatment. An original characterization method is used for the determination of the induced second-order nonlinear profile. A reproducible chi(2) susceptibility of 4.4 +/- 0.4 pm/Volt was achieved for specific poling conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…However, the many kinds of defects and many high energy lone pair electrons are expected to cause large second harmonic generation. 5 In chalcogenide glasses, Ge-S system has high transparency in S-rich composition, and thus this paper reports the second harmonic generation of Ge-S glass system and discusses the mechanism by electron spin resonance ESR and Raman scattering technique for the samples before and after the poling.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the many kinds of defects and many high energy lone pair electrons are expected to cause large second harmonic generation. 5 In chalcogenide glasses, Ge-S system has high transparency in S-rich composition, and thus this paper reports the second harmonic generation of Ge-S glass system and discusses the mechanism by electron spin resonance ESR and Raman scattering technique for the samples before and after the poling.…”
Section: Introductionmentioning
confidence: 98%
“…Some of them are poling under irradiation of UV light called photoinduced, 3 using seed laser incident beam called optical poling 4 and corona poling. 5 With respect to the mechanism, the orientation of dipoles and the process through x 3 are still controversial. But, the large second harmonic generation values have been obtained for UV-poled SiO 2 glass, 3 and optical-poled As 2 S 3 glass.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recent works have demonstrated that large values of second order nonlinear optical coefficient ͓ ͑2͒ ͔ can be obtained in thermally poled inorganic glasses or transparent glass ceramics. [1][2][3] Because of the good thermal, optical, and mechanical stabilities of such materials, they can be considered as potential candidates in this domain.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this paper is concerned with silicate glasses it is important to note that poling has been performed on various other glasses, including tellurite, 42) chalcogenide, 43) silicon oxynitride, 15) and on other materials including polymers and of course non-linear crystals such as LiNbO3. This section considers the poling of several different bulk silicate glasses.…”
Section: Poling Various Glassesmentioning
confidence: 99%